Retention of fatty acyl desaturase 1 (fads1) in elopomorpha and cyclostomata provides novel insights into the evolution of long-chain polyunsaturated fatty acid biosynthesis in vertebrates - Lopes-Marques, Mónica; Kabeya, Naoki; Qian, Yu; Ruivo, Raquel; Santos, Miguel M.; Venkatesh, Byrappa; Tocher, Douglas R.; Castro, L. Filipe C.; Monroig, Óscar (BMC Evolutionary Biology, 2018)
[Background] Provision of long-chain polyunsaturated fatty acids (LC-PUFA) in vertebrates occurs through the diet or via endogenous production from C18 precursors through consecutive elongations and desaturations. It has been postulated that the abundance of LC-PUFA in the marine environment has remarkably modulated the gene complement and function of Fads in marine teleosts. In vertebrates two fatty acyl desaturases, namely Fads1 and Fads2, encode ∆5 and ∆6 desaturases, respectively. To fully clarify the evolutionary history of LC-PUFA biosynthesis in vertebrates, we investigated the gene repertoire and function of Fads from species placed at key evolutionary nodes. [Results] We demonstrate that functional Fads1Δ5 and Fads2∆6 arose from a tandem gene duplication in the ancestor of vertebrates, since they are present in the Arctic lamprey. Additionally, we show that a similar condition was retained in ray-finned fish such as the Senegal bichir and spotted gar, with the identification of fads1 genes in these lineages. Functional characterisation of the isolated desaturases reveals the first case of a Fads1 enzyme with ∆5 desaturase activity in the Teleostei lineage, the Elopomorpha. In contrast, in Osteoglossomorpha genomes, while no fads1 was identified, two separate fads2 duplicates with ∆6 and ∆5 desaturase activities respectively were uncovered. [Conclusions] We conclude that, while the essential genetic components involved LC-PUFA biosynthesis evolved in the vertebrate ancestor, the full completion of the LC-PUFA biosynthesis pathway arose uniquely in gnathostomes. We acknowledge Fundação para a Ciência e a Tecnologia for the support to M.L.-M (SFRH/BD/84238/2012). LFCC research is supported by Norte2020 and FEDER (Coral - Sustainable Ocean Exploitation - Norte-01-0145-FEDER-000036) a project supported by the North Portugal Regional Operational Program (NORTE 2020), under the PORTUGAL 2020 Partnership Agreement, through the European Regional Development Fund (ERDF). The funding bodies played no role in ...